Interferon Gamma in Leishmaniasis - Kima, Peter E.; Soong, Lynn (Frontiers in Immunology, 2013)
Leishmaniasis is a complex disease that is caused by parasites of the Leishmania genus. Leishmania are further classified into several complexes, each of which can engage in distinct interactions with mammalian hosts resulting in differing disease presentations. It is therefore not unexpected that host immune responses to Leishmania are variable. The induction of interferon gamma (IFN-γ) and response to it in these infections has received considerable attention. In this review, we summarize our current understanding of some of the host responses during Leishmania infections that are regulated by IFN-γ. In addition, studies that explore the nature of parasite-derived molecular mediators that might affect the host response to IFN-γ are also discussed.